Pembinaan Pencatatan Akuntansi Dan Peningkatan Pemasaran Kepada UMKM Aneka Cemilan Endez Mbak Tik - Efriyenty, Dian; Hikmah, Hikmah; Azmiana, Risca (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2024)
SMEs still do not understand financial reports according to SME standards and there is no digital-based marketing media. MSMEs also have difficulty in recording finances, the accounting process is complicated. SMEs have many obstacles, including low education, lack of technological skills and limitations in preparing financial reports. Moreover, MSMEs still do not have the ability to present complete and accurate information. Likewise, in the marketing sector that is not yet known to many people, it is still based on word of mouth or only from relatives or neighbors, there is a lack of knowledge among business actors to market their products using digital. Practical methods, exercises and lectures carried out in solving financial problems of service companies, trading companies and manufacturing companies as well as marketing their products both conventionally and digitally. As intended, this activity involves collecting physical evidence of financial reports and inputting them into the MYOB software and training MSMEs to market their products digitally. So that SME businesses are known to the general public and can record their finances according to standards. And MSMEs can make financial reports independently and can be needed by external parties. The aim of this training is that UKMKM can use financial applications and MSMEs can use marketing media to market their products. The results of the service during two MSME meetings were understanding financial bookkeeping based on micro, small and medium entities in inputting sales and understanding online marketing.